Pengaruh Pemanfaatan Plastik Polyethylene Terephalate Pada Campuran Laston Lapis Pengikat - Habibah, Ifani Mita'ul; Rifqi, Mirza Ghulam; Pranowo, Dadang Dwi (Indonesian Society of Applied Science, 2021)
Plastic Polyethylene Terephthalate (PET) waste can be utilized as an added ingredient in a mixture of fastening concrete asphalt (Laston AC-BC). The purpose of this research is to know the influence of the utilization of PET plastics (Polyethylene Terephthalate) on the layer of concrete asphalt binder (Laston AC-BC) using the Marshall method by referring to the design guidelines and implementation of the heat-paved mixture using plastic waste 2019 and the general specification of Highways 2018. This research is done with the addition of PET worms on the asphalt mixture using a dry process. PET levels added in the asphalt mixture are 4%, 4.5%, and 5% of the weight of the asphalt. After the Marshall testing, the results of PET additions to the Laston AC-BC mixture can improve stability. The highest stability value is the addition of PET 5%. The stability value due to PET addition is greater than without the addition of PET. The best PET replenishment rate for asphalt mixture is 5% because, in addition to high stability value, other Marshall parameters such as Flow, VIM, VMA, VFB, and MQ also qualify for the design guidelines and implementation of the hot paved mixture using plastic waste 2019. Value of Optimum asphalt content (KAO) obtained at a 6% asphalt rate with the addition of PET 5%.